2015
DOI: 10.24839/2164-8204.jn20.2.86
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Perceptions of Inappropriate and Appropriate Facebook Disclosures

Abstract: is the International Honor So ci ety in Psychology, found ed in 1929 for the pur pos es of encouraging, stim u lat ing, and maintaining ex cel lence in schol ar ship, and advancing the sci ence of psy chol ogy. Mem ber ship is open to gradu ate and under gradu ate students 58 SUMMER 2015 PSI CHI JOURNAL OF PSYCHOLOGICAL RESEARCH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Second, this unexpected finding may point to the importance of how behaviors are linguistically expressed online and how researchers frame studies of online interaction. Like some other research regarding the view of inappropriate posts (Bazarova, 2012;Roche et al, 2015), the two posts here are hypothetical in order to address specific aspects of drunken expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, this unexpected finding may point to the importance of how behaviors are linguistically expressed online and how researchers frame studies of online interaction. Like some other research regarding the view of inappropriate posts (Bazarova, 2012;Roche et al, 2015), the two posts here are hypothetical in order to address specific aspects of drunken expression.…”
Section: Discussionmentioning
confidence: 99%
“…First, again influenced by Wolfer's (2014) qualitative findings, this post made it clear that the person doing the post was not 21, so the behavior was illegal. Second based on Wolfer 2014and Hebden and colleagues' (2015) findings about references to vomiting and excessive drunkenness, it implied that the poster vomited, thereby possibly providing "too much information" (Roche, et al, 2015). This "high offense" (HO) post is:…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…In summary, this research contributes to the existing literature in a number of ways. First, this research is qualitative and respondent driven so it identified many themes of inappropriate Roche et al, 2015), but expanding the topics of these posts given the findings of this study. This can be followed with asking respondents whether they have actually seen any of the posts described.Second, future research might want to explore why people of different ages find these types of posts inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al's () findings support previous research aimed at identifying topics that SNS users consider to be inappropriate to post. Sexual content, alcohol consumption, political and religious beliefs, profanity, expression of negative emotion, personal issues, and negative posts about others are commonly endorsed as inappropriate topics to share on Facebook (Muscanell, Ewell, & Wingate, ; Roche, Jenkins, Aguerrevere, Kietlinski, & Prichard, ; Wolfer, ). Similarly, SNS users commonly report deciding against posting opinions, personal information, emotional disclosures, and political content (Sleeper et al, ; Vitak, ).…”
Section: Introductionmentioning
confidence: 99%